Psychological wellbeing of students with trait narcissism - Yi Ming Ho; Kususanto Ditto Prihadi; Po Yi Chan; Kazi Sumaiya Ahsan Kaz; Hirosharani Velayutam (Journal of Education and Learning (EduLearn), 2023)
Previous studies suggested that perceived social support (PSS) significantly contributes to psychological wellbeing (PWB), partially explained by the sense of mattering. Nevertheless, individuals with different personality might perceive social support in different ways from the other. The interaction of PSS with trait narcissism, one of the dark triad personality traits was investigated by collecting data from 141 college students who were recruited purposively and instructed to respond to the scales of PWB, PSS, mattering, and narcissism. Bootstrap analysis with 5,000 samples in 95% confidence interval was utilized to test the moderated mediation hypothesis. The results suggested that individuals with moderate-to-high narcissism levels tend to perceive social support as decreasing their sense of mattering to other people, and as they do not feel they matter, their PWB was negatively affected. Limitations, implications, and suggestions are discussed.